2-1-05. PR interval of electrocardiography is significantly correlated with the findings of cardiac MIBG scintigraphy in Parkinson's disease. Issue 6 (June 2017) - Mochizuki, Hitoshi; Ishii, Nobuyuki; Ugawa, Yoshikazu; Taniguchi, Akitoshi; Sugiyama, Takashi; Shiomi, Kazutaka; Nakazato, Masamitsu
Abstract : Cardiac 123I-metaiodobenzylguanidine scintigraphy (MIBG) has been used to assess the postganglionic presynaptic cardiac sympathetic nerve endings and demonstrated an uptake reduction in patients with Parkinson's disease (PD). On the other hand, epidemiologic research showed that electrocardiography (ECG) abnormalities occurred prior to motor signs in PD. In this study, we investigated whether the electrical conduction system of the heart was impaired in PD. Clinical features, ECG and MIBG parameters were analyzed in 191 patients with PD, 42 with multiple system atrophy (MSA) and 124 normal controls (NL). PR interval in ECG was significantly longer in patients with PD than in NL, and the PR interval negatively correlated with early and delayed heart-to-mediastinum ratios in MIBG scintigraphy in PD and MSA patients. No significant differences were detected in QTc between the three groups. This study is the first to demonstrate the prolongation of the PR interval in PD and its correlation with MIBG scintigraphy parameters. The PR prolongation must reflect some sympathetic system abnormality since it is mainly controlled by sympathetic nervous system. Repeated measures of PR interval might be one alternative tool to predict autonomic dysfunction in a part of PD patients.